I see, and I hunt: the link between gastronomy online reviews, involvement and behavioural intention towards ethnic food - Xin, Jean Lim; Ng, Siew Imm; Chuah, Francis; Tat, Huei Cham; Rozali, Aifa (Emerald, 2020)
Purpose: Despite the growth of social networking websites as hybrid promotional tools, the empirical research that is currently available in explaining the consequences of gastronomy online reviews on ethnic food behavioural intention is limited. The purpose of this paper is to adopt a novel approach to explore Gen-Y tourists’ behavioural intention by proposing “involvement” as a mediator in improvising Wang et al.’s model. In other words, the more tourists enjoy reading gastronomy online reviews and gain benefits like inspiring taste desire, forming taste awareness and facilitating interpersonal interaction, the more they will become actively involved in searching gastronomy online reviews for ethnic food, subsequently manifesting in higher behavioural intention. Design/methodology/approach: To test the research model, a questionnaire was developed and distributed to Gen-Y tourists in Malaysia using the purposive sampling technique. Partial least squares–structural equation modelling was applied to analyse the data collected from a sample of 748 responses. Findings: This study provides empirical findings based on the direct relationship between gastronomy online review dimensions and the behavioural intention towards ethnic food. In addition, the indirect influence of the constructs for behavioural intention through involvement and the moderating effect of variety seeking were found. Indeed, when involvement increases as a result of reading online reviews, behavioural intention is enhanced. In fact, if the individual is a variety seeker, the behavioural intention could likewise be enhanced. Practical implications: This paper provides suggestions and valuable insight for tourism authorities and ethnic food eateries in using gastronomy online reviews for promoting ethnic food and gastronomy tourism. For example, food eateries can motivate reviewers to include attractive and useful content by facilitating how the gastronomy reviewer retrieves information (e.g. ingredients, price, and food health value and food tradition) concerning the eatery. Additionally, rewards and incentives such as offering vouchers to reviewers in order to gain attractive and interesting reviews could be considered. Finally, the variety-seeking goal of tourists can be attained by relocating ethnic food restaurants or stalls at centralised or designated areas, where a variety of ethnic foods are conveniently accessible to tourists. Originality/value: This paper systematically discusses how gastronomy online reviews influence the behavioural intention of tourists to taste ethnic food in the context of Malaysia. The inclusion of the mediator (involvement) and moderator (variety seeking) added a significant increment to the total variance explained in behavioural intention.